High-velocity OH megamasers in IRAS 20100−4156: evidence for a supermassive black hole - Harvey-Smith, L; Allison, J; Green, J; Bannister, K; Chippendale, A; Edwards, P; Heywood, I; Hotan, A; Lenc, E; Marvil, J; McConnell, D; Phillips, C; et al. (Oxford University Press, 2016)
We report the discovery of new, high-velocity narrow-line components of the OH megamaser in IRAS 20100−4156. Results from the Australian Square Kilometre Array Pathfinder (ASKAP)'s Boolardy Engineering Test Array (BETA) and the Australia Telescope Compact Array (ATCA) provide two independent measurements of the OH megamaser spectrum. We found evidence for OH megamaser clumps at −409 and −562 km s−1 (blue-shifted) from the systemic velocity of the galaxy, in addition to the lines previously known. The presence of such high velocities in the molecular emission from IRAS 20100−4156 could be explained by a ∼50 pc molecular ring enclosing a ∼3.8 billion solar mass black hole. We also discuss two alternatives, i.e. that the narrow-line masers are dynamically coupled to the wind driven by the active galactic nucleus or they are associated with two separate galactic nuclei. The comparison between the BETA and ATCA spectra provides another scientific verification of ASKAP's BETA. Our data, combined with previous measurements of the source enabled us to study the variability of the source over a 26 yr period. The flux density of the brightest OH maser components has reduced by more than a factor of 2 between 1988 and 2015, whereas a secondary narrow-line component has more than doubled in the same time. Plans for high-resolution very long baseline interferometry follow-up of this source are discussed, as are prospects for discovering new OH megamasers during the ASKAP early science programme.